2015
DOI: 10.1007/s00330-015-3878-x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of malignant from benign soft tissue tumours: use of additive qualitative and quantitative diffusion-weighted MR imaging to standard MR imaging at 3.0 T

Abstract: Objectives To determine the added value of diffusionweighted imaging (DWI) to standard magnetic resonance imaging (MRI) to differentiate malignant from benign soft tissue tumours at 3.0 T. Methods 3.0 T MR images including DWI in 63 patients who underwent surgery for soft tissue tumours were retrospectively analyzed. Two readers independently interpreted MRI for the presence of malignancy in two steps: standard MRI alone, standard MRI and DWI with qualitative and quantitative analysis combined. Results There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
58
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 22 publications
(40 reference statements)
5
58
1
1
Order By: Relevance
“…Nagata et al [12] reported that three of five giant cell tumors of the tendon sheath (tenosynovial giant cell tumor) showed low ADCs, mimicking malignant soft tissue tumors. Since our case revealed hypointense to intermediate signal on T2-weighted images and low ADCs on DWI despite the benign appearances, giant cell tumor was the favorable diagnosis [13]. However, the mass was not a bone lesion, so tenosynovial giant cell tumor (giant cell tumor of the tendon sheath) was included in our differential diagnosis, even though the lesion was not located adjacent to a tendon in our patient.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Nagata et al [12] reported that three of five giant cell tumors of the tendon sheath (tenosynovial giant cell tumor) showed low ADCs, mimicking malignant soft tissue tumors. Since our case revealed hypointense to intermediate signal on T2-weighted images and low ADCs on DWI despite the benign appearances, giant cell tumor was the favorable diagnosis [13]. However, the mass was not a bone lesion, so tenosynovial giant cell tumor (giant cell tumor of the tendon sheath) was included in our differential diagnosis, even though the lesion was not located adjacent to a tendon in our patient.…”
Section: Discussionmentioning
confidence: 64%
“…However, the mass was not a bone lesion, so tenosynovial giant cell tumor (giant cell tumor of the tendon sheath) was included in our differential diagnosis, even though the lesion was not located adjacent to a tendon in our patient. On DWI a giantcell-containing benign soft tissue tumor sometimes shows impeded diffusivity (water movement) mimicking malignancy [12,13], and knowing these DWI features in addition to the standard MR findings could help suggest a benign soft tissue lesion. Hemangioma and myositis ossificans were included in the differential diagnosis because of mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the selection of b‐value can have marked effects on measured ADC values. When low b‐values are used, ADC can be compromised by perfusion effects, as perfusion may artificially increase the ADC values of malignant lesions . However, the optimal number and scale of b value selection are controversial .…”
Section: Discussionmentioning
confidence: 99%
“…Until now, there have been several studies to evaluate the clinical usefulness of DWI and DCE‐MRI, respectively, to differentiate between benign and malignant soft‐tissue tumors. However, there are few studies for the differential diagnosis of soft‐tissue tumors by considering both DWI and DCE‐MRI.…”
mentioning
confidence: 99%
“…We are unable to describe the exact etiology of this phenomenon. Nevertheless, ADC value is certainly affected by b value, as well as magnetic field strength (18). We investigated whether the addition of DWI (b value of 400 or 1000) to the routine MR image influenced the sensitivity, specificity, or accuracy of the diagnostic differentiation between benign and malignant lesions.…”
Section: Discussionmentioning
confidence: 99%